(untitled) (Scientific journal of the Fergana State University, 2024)
The theoretical basis of the development of social competence of students based on the integrative teaching of pedagogical sciences, the methodical system of developing the social competence of students based on the integrative teaching of pedagogical sciences, the effectiveness of the development of social competence of students on the basis of the integrative teaching of pedagogical sciences are studied in the article. Also, the content and didactic foundations of the concept of social competence were analyzed.